2013
DOI: 10.5668/jehs.2013.39.1.48
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Toxicity Assessment of Aluminum Oxide Nanoparticles via Nasal Instillation Exposure

Abstract: Objective: The use of nanoparticle products is expected to present a potential harmful effect on consumers. Also, the lack of information regarding inhaled nanoparticles may pose a serious problem. In this study, we addressed this issue by studying pulmonary toxicity after nasal instillation of Al-NPs in SD rats. Methods: The animals were exposed to Al-NPs at 1 mg/kg body weight (low dose), 20 mg/kg body weight (medium dose) and 40 mg/kg body weight (high dose). To determine pulmonary toxicity, bronchoalveolar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
(5 reference statements)
0
10
1
Order By: Relevance
“…More specifically, this was reflected by an increase in the absolute and relative lung weights in the 5 mg/m 3 group during exposure. This was in contrast to a previous study where intratracheal instillation of Al 2 O 3 NPs induced no changes in organ weight ( 7 ).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…More specifically, this was reflected by an increase in the absolute and relative lung weights in the 5 mg/m 3 group during exposure. This was in contrast to a previous study where intratracheal instillation of Al 2 O 3 NPs induced no changes in organ weight ( 7 ).…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, hematology and serum biochemistry results showed that there were no systemic effects related to the exposure to Al 2 O 3 NPs. Kwon et al showed similar results in SD rats, although the exposure to Al 2 O 3 NPs was through intratracheal instillation ( 7 ). Although no systemic effects were observed in the present study after Al 2 O 3 NP exposure, including body weight loss and clinical symptoms, the toxicological effects related to Al 2 O 3 NPs exposure were mainly observed in the lungs.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations